2003
DOI: 10.1002/jbm.a.20028
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent versus continuous stretching effects on osteoblast‐like cells in vitro

Abstract: The objective of this study was to quantify and compare stretch-mediated responses of primary rat osteoblast-like cells to uniform cyclic strain applied intermittently or continuously. Primary rat osteoblast-like cells were seeded and cultured in silicone rubber dishes for 2 days. They were then subjected to 1000 microstrains at 1 Hz for periods of 60 consecutive minutes or to a series of 15-min stretch followed by 15-min rest, until a total stretch of 60 min. After stretching, cells were incubated and assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
1
40
1
Order By: Relevance
“…Jacobs et al showed that an inserted short-term rest (as short as 10 s) in oscillatory flow increased the frequency and magnitude of [ intermittent stretching was more potential than continuous stretching in primary osteoblasts, by analyzing the DNA content, ALP activity, and calcium deposition. 23) In the present study, we showed similar recovery of mechanosensitivity during inserted rest periods (Fig. 3).…”
Section: Discussionsupporting
confidence: 85%
“…Jacobs et al showed that an inserted short-term rest (as short as 10 s) in oscillatory flow increased the frequency and magnitude of [ intermittent stretching was more potential than continuous stretching in primary osteoblasts, by analyzing the DNA content, ALP activity, and calcium deposition. 23) In the present study, we showed similar recovery of mechanosensitivity during inserted rest periods (Fig. 3).…”
Section: Discussionsupporting
confidence: 85%
“…In order to further enhance membrane bioactivity, we also designed and used ELRs with an additional RGDS sequence (HAP-RGDS) in order to promote integrin-mediated cell adhesion. Mineralization experiments, with and without cells, were con-ducted in simulated body fluid (SBF) [29] in both static and dynamic experimental conditions since some studies have reported an increase of cell-mediated mineralization under applied strain [30]. In this work, Smooth HAP membranes tested under static conditions reproducibly and significantly increased their mineral-ization compared to all other tested membranes as revealed by the calcium content assay (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…The samples were maintained under agitation overnight at room temperature. The supernatant was recollected and calcium content was determined using an orthocresolphthalein complexone method [30]. The calcium content was measured on a fluorescence microplate reader (Bio-Tek Instruments Inc., Winooski, VT, USA) at 570 nm, and determined by extrapolating known values from a standard curve.…”
Section: Calcium Contentmentioning
confidence: 99%
“…Moreover, Prodanov et al (28) applied a different cyclic strain profile than the one used in this study, which might have affected the results. In particular, they applied an intermittent cyclic strain instead of a continuous one, and this difference is known to affect the behavior of cells (46). In addition, changing the model parameters to match specific experimental results might be challenging, due to the large number and high level of interdependency of the parameters.…”
Section: Discussionmentioning
confidence: 99%